Allometric growth patterns in a hybrid triploid-sturgeon (Huso huso♀x Acipenser baeri♂) during early development - Eagderi, S.; Bahrami Ziarani, M.; Poorbagher, H.; Farahmand, H.; Eshaghzade, H. (2017)
Allometric growth pattern is a phenomena during early development of fishes. This research was conducted to study the allometric growth patterns of a hybrid triploid sturgeon (Acipenser baeri♂ x Huso huso♀) during early developmental stage up to 50 day post hatching (dph). Morphometric parameters of this study obtained from 2D pictures of specimens using the software ImageJ and allometric growth pattern was calculated as a power function of total length using non-transformed data: Y=axb. The results revealed that during early development of the triploid sturgeon after hatching, head and tail regions have positive allometric growth pattern that can be as result of importance vital functions, including swimming, respiration and sensory systems during this period. The inflexion points of the most body parts have been occurred prior 25dph and afterward their growth patterns were isometric. Despite the genetic difference between the hybrid triploid sturgeon with its parents, the results showed that its allometric growth patterns have many similarities with them. This results, also, provide evidence that the phenotypic plasticity plays important role in regulation of the body shape during early development. Published